Penerapan Mesin Pembuatan Pakan Ikan Alternatif pada Kelompok Wanita Tani “Makmur Berkah” di Desa Kutasari Kecamatan Baturraden: Implementation of an Alternative Fish Feed Making Machine in the "Makmur Berkah" Farming Women's Group in Kutasari Village, Baturraden District - Saputra, Eqwar; Mulia, Dini Siswani; Juanita, Juanita; Yasinta, Syaukaty (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
KWT Makmur Berkah is involved in agriculture and fisheries, utilizing land of 150 tiles (approximately 2,100 m²). In agriculture, members cultivate peanuts, chili peppers, and vegetables. In fisheries, they practice polyculture with various fish species. Currently, the fish feed used is a mix of kitchen spices and pellets. Interviews revealed that the feeding practices are suboptimal, as they focus solely on increasing fish size without addressing nutritional quality. This community service project aims to improve the knowledge and skills of KWT Makmur Berkah members in producing alternative fish feed. The project began with an overview of the importance of high-quality fish feed, followed by training in the production of alternative feed. Participants then took part in demonstrations and hands-on practice with fish feed pellet machines and learned how to maintain these machines. After the initial implementation, monitoring and evaluation were carried out, alongside periodic support to ensure the program’s ongoing success. A total of 20 KWT Makmur Berkah members participated in the project. The project’s results were significant. Participants, particularly women, not only successfully learned to operate the feed pellet machines independently but also reported high levels of satisfaction with the tool’s ease of use and efficiency. Feedback from the training was overwhelmingly positive, with many members noting that the program significantly enhanced their fish farming practices.